Long Non-coding RNAs Genes Polymorphisms and Their Expression Levels in Patients With Rheumatoid Arthritis - Zhang, Tian-Ping; Zhu, Bang-Qiang; Tao, Sha-Sha; Fan, Yin-Guang; Li, Xiao-Mei; Pan, Hai-Feng; Ye, Dong-Qing (Frontiers in Immunology, 2019)
LncRNAs are increasingly recognized to play important roles in multiple autoimmune diseases. This study aimed to evaluate the association of four lncRNAs (ANRIL, lnc-DC, MALAT1, ZFAS1) genes single nucleotide polymorphisms (SNPs) with susceptibility to rheumatoid arthritis (RA) patients, as well as their expression levels. Seventeen SNPs of the four lncRNAs were genotyped in a cohort of 660 RA patients and 710 controls using improved multiple ligase detection reaction (iMLDR). The lncRNAs expressions in peripheral blood mononuclear cells (PBMCs) from 120 RA patients and 120 controls were detected by qRT-PCR. No significant differences were found for the allele and genotype frequencies distribution of ANRIL SNPs (rs1412830, rs944796, rs61271866, rs2518723, rs3217992), lnc-DC SNPs (rs7217280, rs10515177), MALAT1 SNPs (rs619586, rs4102217, rs591291, rs11227209, rs35138901), ZFAS1 SNPs (rs237742, rs73116127, rs6125607, rs6125608) between RA patients and normal controls (all P ＞ 0.05). The genotype effects of dominant and recessive models were also evaluated, but no significant association was found. In addition, our results demonstrated that the rs944796 G allele, rs2518723 T allele, rs3217992 T frequencies were significantly associated with anti-CCP in RA patients (all P ＜ 0.05). The haplotype CGTA frequency for ZFAS1 was significantly higher in RA patients (P = 0.036). Compared with normal controls, the expression levels of ANRIL, lnc-DC, MALAT1, ZFAS1 in PBMCs were significantly reduced in RA patients (all P ＜ 0.001). Moreover, ZFAS1 expression was negatively associated with CRP in RA patients (P=0.002). In summary, ANRIL, lnc-DC, MALAT1, and ZFAS1 genes SNPs were not associated with RA susceptibility, while altered ANRIL, lnc-DC, MALAT1, ZFAS1 levels in RA patients suggested that these lncRNAs might play a role in RA.